2017
DOI: 10.1002/med.21478
|View full text |Cite
|
Sign up to set email alerts
|

Potential cardiac risk of immune‐checkpoint blockade as anticancer treatment: What we know, what we do not know, and what we can do to prevent adverse effects

Abstract: Cancer immunotherapy has become a well-established treatment option for some cancers after the development of a family of drugs targeting the so-called immune checkpoints, such as CTLA4 and PD-1 with PD-L1. These co-receptors/ligands inhibit the activation of T-cell, thus preventing an excessive inflammatory response. Tumors exploit these pathways to induce immune tolerance to themselves. Thus, the main effect of checkpoint-blocking drugs is to awake an immune response primarily directed against cancer cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…25 Although typically reversible, numerous cases of fulminant myocarditis have been described. 26 Overall, the lower prevalence of conventional cardiac risk factors in paediatrics may decrease the incidence of the acute cardiac effects described with many molecularly targeted agents in the adult setting. 17,20 However, treating oncologists must be mindful of these potential toxicities and have a low threshold for detailed cardiac evaluations and cardiology referral when utilizing these agents.…”
Section: 2-348)mentioning
confidence: 99%
“…25 Although typically reversible, numerous cases of fulminant myocarditis have been described. 26 Overall, the lower prevalence of conventional cardiac risk factors in paediatrics may decrease the incidence of the acute cardiac effects described with many molecularly targeted agents in the adult setting. 17,20 However, treating oncologists must be mindful of these potential toxicities and have a low threshold for detailed cardiac evaluations and cardiology referral when utilizing these agents.…”
Section: 2-348)mentioning
confidence: 99%
“…Although the side effects of immunotherapy are less than chemotherapeutic agents (4), immunotherapy still may cause dermatological (reticular, maculopapular erythematous rash, and mucositis), gastrointestinal (diarrhea and colitis), hepatic (elevation of liver enzymes in serum), and endocrine adverse effects (involving pituitary, adrenal, or thyroid glands). This is because the immune response triggered by these drugs is not completely tumor-specific (6). The management of their adverse events usually includes various forms and regimens of corticosteroids (7).…”
Section: Introductionmentioning
confidence: 99%
“…The exact incidence is not clear. Animal experiments have observed that T lymphocytes infiltrate coronary endothelium and lipid plaques after ICI application, increasing plaque instability, which may be the pathophysiological basis of myocardial ischemia after ICI administration …”
Section: Clinical Manifestationmentioning
confidence: 99%
“…There is currently no high‐quality study to investigate the characteristics of patients at high risk of developing ICI‐associated cardiotoxicity. However, the following groups may require special attention empirically: first, patients receiving the combination of two kinds of ICI drugs or the usage of ICI drugs combined with other antitumor drugs with cardiotoxicity (such as tyrosine kinase inhibitors); second, patients with a history of cardiac lesions caused by previous usage of antitumor drugs; and third, the patients with cardiac diseases (such as coronary heart disease, heart failure, myocarditis and valve diseases) …”
Section: Early Detection Of Ici‐associated Cardiotoxicitymentioning
confidence: 99%